Selenomethionine Suppressed TLR4/NF-κB Pathway by Activating Selenoprotein S to Alleviate ESBL Escherichia coli-Induced Inflammation in Bovine Mammary Epithelial Cells and Macrophages - Zhuang, Cuicui; Liu, Gang; Barkema, Herman W.; Zhou, Man; Xu, Siyu; ur Rahman, Sadeeq; Liu, Yongxia; Kastelic, John P.; Gao, Jian; Han, Bo (Frontiers in Microbiology, 2020)
Inflammation is the hallmark of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli-induced bovine mastitis. Organic selenium can activate pivotal proteins in immune responses and regulate the immune system. The present study aimed to investigate whether selenomethionine (SeMet) attenuates ESBL E. coli-induced inflammation in bovine mammary epithelial cells (bMECs) and macrophages. Cells were treated with 0, 5/10, 10/20, 20/40 or 40/60 μM SeMet for 12 h and/or inoculated with ESBL-E. coli (MOI=5) for 4/6 h, respectively. We assessed inflammatory responses, including selenoprotein S (SeS), Toll-like receptor 4 (TLR4), Ikappa-B (IκB), phospho-NF-κB p65 (Ser536), IL-1β, tumor necrosis factor-α (TNF-α) and lactate dehydrogenase (LDH) activities. Treatment with 40/60 μM SeMet promoted cell viability and inhibited LDH activities in both bMECs and macrophages. Inoculation with ESBL-E. coli reduced cell viability, which was attenuated by SeMet treatment in bMECs and macrophages. SeMet increased ESBL E. coli-induced downregulation of SeS and decreased LDH activities, TLR4, IκB, phospho-NF-κB p65 (Ser536), IL-1β and TNF-α protein expressions in bMECs and macrophages. In addition, knockdown of SeS promoted protein expression of TLR4-mediated NF-κB pathway and BAY 11-708 inhibited TNF-α and IL-1β protein levels in bMECs and macrophages after ESBL-E. coli treatment. Moreover, ESBL-E. coli inoculation increased monocyte chemoattractant protein 1 (MCP-1), C–C motif ligand 3 (CCL-3) and CCL-5 mRNA expressions in bMECs. In conclusion, ESBL-E. coli induced expression of MCP-1, CCL-3 and CCL-5 in bMECs and then recruited and activated macrophages, whereas SeMet attenuated ESBL E. coli-induced inflammation through activated SeS-mediated TLR4/NF-κB signaling pathway in bMECs and macrophages.